Anti-inflammatory, hepatoprotective and antioxidant activity of ellagitannin isolated from Melaleuca styphelioides. (September 2020) - Al-Sayed, Eman; Korinek, Michal; Esmat, Ahmed; Chen, Guan-Yu; Cheng, Yuan-Bin; Hsieh, Pei-Wen; Chen, Bing-Hung; Hwang, Tsong-Long
Abstract: Ellagitannins have a marked antioxidant effect and can prevent liver injury induced by free radicals. An undescribed ellagitannin named styphelioidin was isolated from Melaleuca styphelioides Sm. The structure of styphelioidin was elucidated by using various spectroscopic methods. The hepatoprotective activity of styphelioidin (25, 50, and 100 μM) was tested using the CCl4 -challenged HepG2 cell model by measuring alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in HepG2 cells treated with styphelioidin for 1 h followed by 40 mM CCl4 . Glutathione (GSH), superoxide dismutase activity (SOD) and lipid peroxidation (MDA) were evaluated to determine the mechanisms of the hepatoprotective activity. Styphelioidin significantly reduced the levels of ALT, AST, and MDA at all tested concentrations. Moreover, it conferred a marked increase in the GSH levels and the SOD activity compared to the CCl4 -treated groups. Styphelioidin also exerted DPPH· radical-scavenging effects with an IC50 value of 3.67 μM. Results indicated the hepatoprotective therapeutic potential of styphelioidin comparable to silymarin. Moreover, anti-inflammatory activity was assessed and styphelioidin inhibited fMLF/CB-induced elastase release in human neutrophils with IC50 2.51 μM. Cell-free experiments with human neutrophil elastase indicated a direct enzymatic inhibitory effect of styphelioidin on the enzyme activity (IC50 2.58 μM). The potential of styphelioidin to interact with human neutrophil elastase binding sites was further confirmed by molecular docking of styphelioidin into human neutrophil elastase crystal structure using AutoDock 4.2. Styphelioidin represents a potent hepatoprotective and antioxidant agent with effects on ALT, AST, MDA, GSH, and SOD comparable to silymarin. The beneficial anti-elastase properties hold the potential for drug development against elastase-related inflammatory diseases. This study highlights a promising natural hepatoprotective and anti-inflammatory candidate derived from M. styphelioides . Graphical abstract: Image 1 Highlights: Undescribed ellagitannin, styphelioidin, was isolated from Melaleuca styphelioides. Styphelioidin showed potent hepatoprotective activity comparable to silymarin. Styphelioidin inhibited fMLF/CB-induced elastase release in human neutrophils. Styphelioidin directly inhibited human neutrophil elastase enzymatic activity. Styphelioidin interacted with human neutrophil elastase binding sites in silico.